Human-animal interaction and cattle handling practices in Colombian livestock auctions - Herrán, Lucia (2017)
The objective of the study was to evaluate the human-animal interaction (HAI) and the handling practices at a livestock market in Medellin, Colombia. Data was collected at four livestock auctions in June 2014. A total of 720 bovines were distributed into 241 and 28 groups during the weighing and driving to the corral respectively. Findings during the veterinary inspection, as well as tactile, auditory and visual interactions of cattle handlers and behavioral responses of cattle were evaluated. In the veterinary inspection, 19.5% of the groups were observed, especially due to open wounds (38.3%). In the weighing area, there were 824 interactions, predominantly visual (44.1%) and then tactile (30.1%) and auditory (25.8%); however, 73.0, 66.4 and 88.4% of the animals had no behavioral response to visual, tactile and auditory interactions, respectively. Twenty-four interactions were recorded during driving to corrals, with tactile predominance (42.5%) over auditory (30.8%) and visual (26.6%); however, most of the groups presented only behavioral response to tactile interactions (68%). Positive handling interactions such as whistling, waving the instrument, and raising hands generated few behavioral responses and quieter animal handling. On the other hand, hitting, punching, and screaming provoked greater reactivity and agonistic behaviors in the animals.